Profile variables as discriminants of college admission test results a path analysis - Ydio, Liezl A.; Roaring, Bobby F. (2015)
This study focused on how the profile variables such age, family income, achievement motivation and GPA contribute to the causality of the college admission test result. Path analysis is a straightforward extension of multiple regressions which aims is to provide estimates of the magnitude and significance of hypothesized casual connections between sets of variables. This paper presents the path analysis i determining the causal connection of profile variables such as age, family income, achievement motivation and GPA to the college admission result.
The study shows that family income and GPA have a direct effect on the college admission test result, while age and achievement motivation have an indirect effect on the admission test result. Based on on the results, path model is a good fit.
Keywords: Admission test score; Personality and motivation